Health Literacy and Self-Management Among Older Persons with Metabolic Syndrome - Noiboontun, Rumpaipun; Panuthai, Sirirat; Suwankruhasn, Nattaya (Nursing Journal CMU, 2022)
Older persons with metabolic syndrome having a high self-management ability are more likely to reduce the chance of developing complications. This correlative descriptive research aimed to investigate health literacy, self-management, and the relationship between health literacy and self-management among older persons with metabolic syndrome. The participants were 88 older persons with metabolic syndrome who had received medical treatment at the Tambon Health Promoting Hospital, Doi Saket, Chiang Mai during June - August 2021. The data collection tools were questionnaires regarding the health literacy of older persons with metabolic syndrome and the self-management of older persons with metabolic syndrome. Data were analyzed using descriptive statistics and Pearson’s product-moment correlation. The results revealed that older persons with metabolic syndrome had health literacy and self-management at a moderate level. Furthermore, health literacy positively correlated with self-management at a moderate level with a statistical significance of 0.01 (r = 0.661). The results of this study show basic information for health care personnel to plan for self-management enhancement among older persons with metabolic syndrome.